Multicultural education through Pancasila-based visual learning media : A research and development study - Aulia, Syifa Siti; Marzuqi, Yasir; Dewi, Ainun Karuni; Andini, Diah Yola; Rahmania, Annisa; Zulfikar, Muhammad; Setianingsih, Aprilia (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
This study aims to develop educational media grounded in Pancasila values to enhance multicultural education in higher education. In a diverse society like Indonesia, education that promotes democracy, justice, and inclusivity is becoming increasingly vital. Employing a Research and Development (R&D) methodology based on the Borg & Gall model, this study includes stages of design, development, expert validation, limited user testing, and dissemination. The resulting product comprises five thematic educational media tools, each representing a dimension of multicultural education grounded in one or more principles of Pancasila. Validation was conducted by two civic education experts and five students who had previously taken a Multicultural Education course. Findings indicate that all media were deemed appropriate, with an average evaluation score exceeding 80. Expert feedback highlighted the need for improvements in visual aesthetics, image clarity, and the integration of the curriculum. The study demonstrates that Pancasila-based educational media not only enhance students’ cognitive understanding but also foster critical awareness and inclusive attitudes in civic life. The developed media show strong potential for integration into both Civic Education and Multicultural Education courses at the tertiary level.